High-temperature-resistant strong-bonding repair material as well as preparation method and application thereof
Components A and B prepared using materials such as imide modified polysiloxane and terminal vinyl polysiloxane, the binding force of existing repair materials with resin-based thermally insulating composite materials at high temperatures is solved. The poor problem is that high-temperature strong bonding and anti-shrink performance are achieved, and the heat insulation composite materials are used for rapid repair and efficient heat protection of high-speed aircraft.
Patent Information
- Application Number
- CN202411218428.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2024-12-27
AI Technical Summary
The poor bonding force of existing repair materials with resin-based thermal insulation composite materials under high temperature conditions leads to the problem of high-temperature debonding and ablation and thinning, and cannot effectively repair the thermal protection defects on the surface of high-speed aircraft.
Use imide modified polysiloxane and end vinyl polysiloxane to form films, heat-resistant and corrosion-resistant composite fillers, thermal insulation fillers, composite ceramic powders, reinforced fillers, platinum complex catalysts and anti-prevention Component A composed of poisoning agent and component B composed of hydrogen-containing polysiloxane are mixed to produce high-temperature-resistant and strong bonding repair materials, which are used to repair damaged parts of the heat-insulating composite materials.
It realizes rapid repair of heat-insulating composite materials at room temperature, has high temperature and high bonding strength, good anti-shrink performance, and can maintain the shear strength greater than 1.0MPa at 800℃×5min, which is suitable for efficient heat protection and repair of high-speed aircraft.
Smart Images

Figure CN119193101A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of defect repair of resin-based thermal insulation composite materials, and further to a high-temperature resistant strong bonding repair material and a preparation method and application thereof. Background Art
[0002] During the high-speed flight of a high-speed aircraft, the surface of the aircraft will be subjected to severe aerodynamic heating, and its surface temperature will reach more than one thousand degrees. Under such high-temperature aerodynamic heat conditions, the components inside the aircraft will not be able to work normally. Therefore, in order to ensure the normal operation of the aircraft, the surface of the aircraft needs to be thermally protected. Resin-based anti-thermal insulation composite materials (hereinafter referred to as thermal insulation composites) are one of the main solutions for large-area protection of the surface of high-speed aircraft. They are mainly high-efficiency thermal insulation materials with phenolic resin as the matrix, reinforced by fibers, etc., and introduced into the micro-nano pore structure of aerogel. Although thermal insulation composites have good thermal insulation properties, their strength is relatively low and they are brittle. They are prone to cracks, pits and other damage during machining, assembly, transfer and other processes. Once defects occur in the thermal insulation composite, it may lead to thermal protection failure, and in severe cases, it may cause accidents such as thermal disintegration of the aircraft. Therefore, once the thermal insulation composite is damaged by collision and cannot be quickly repaired, the aircraft will face the situation of being unable to work.
[0003] As the flight speed of aircraft becomes higher and higher, the aerodynamic heating environment faced by the repair materials is becoming more and more severe, which means that the repair materials not only need to have high erosion resistance, but also need to have high-temperature shear strength to prevent debonding failure due to poor high-temperature bonding with lightweight thermal insulation materials at high temperatures. Existing repair materials are mainly divided into two categories based on different film-forming materials, namely organic repair materials and inorganic repair materials; among them, inorganic repair materials have poor thermal matching with lightweight thermal insulation materials and are not suitable for repairing thermal insulation composites; conventional organic repair materials use epoxy, polyurethane, and rubber as film-forming materials, which are mainly used for repairing microporous defects on the surface of furniture, lathes, etc., and their heat resistance and ablation resistance are poor; high-temperature resistant repair materials with silicone as film-forming materials mainly focus on residual carbon rate and ablation rate at high temperatures, but their own strength and bonding strength at high temperatures are low, and the high-temperature bonding with thermal insulation composites is poor. Problems such as high-temperature debonding of repair materials are prone to occur during high-speed flight. Summary of the invention
[0004] In order to solve the problems existing in the prior art, the present invention provides a high temperature resistant heat insulation repair material and its preparation method and application. The present invention provides a high temperature resistant heat insulation repair material with good matching with heat insulation composite materials, high bonding strength at high temperature, and good anti-scouring performance, which solves the problems of poor high temperature bonding strength of the repair material, easy debonding from the heat insulation composite material at high temperature, and rapid ablation and thinning, so as to realize rapid room temperature repair of the heat insulation composite material.
[0005] One of the purposes of the present invention is to provide a high temperature resistant strong bonding repair material.
[0006] The high temperature resistant strong bonding repair material of the present invention comprises component A and component B, wherein component A and component B are prepared from raw materials comprising the following components respectively:
[0007] Component A includes a composite film-forming material, a heat-resistant and anticorrosive composite filler, a heat-insulating filler, a composite ceramic powder, a reinforcing filler, a platinum complex catalyst, an anti-poisoning agent, and a second solvent;
[0008] Component B includes vinyl-terminated polysiloxane and hydrogen-containing polysiloxane;
[0009] The weight ratio of component A to component B is (0.5-3):1;
[0010] In component A:
[0011] The weight ratio of the heat-resistant and anticorrosive composite filler to the composite film-forming material is 1:(1-9);
[0012] The weight ratio of the thermal insulation filler to the composite film-forming material is 1:(1-6);
[0013] The weight ratio of the composite ceramic powder to the composite film-forming material is 1:(2.5-10);
[0014] The weight ratio of the reinforcing filler to the composite film-forming material is 1:(2-10);
[0015] The weight of the platinum element in the platinum complex catalyst is 5-500ppm of the total weight of the A component;
[0016] The anti-poisoning agent is 0.5-5wt% of the composite film-forming material;
[0017] The second solvent is 5%-30% of the total weight of the composite film-forming material, the heat-resistant and corrosion-resistant composite filler, the thermal insulation filler, the composite ceramic powder and the reinforcing filler;
[0018] In component B:
[0019] The weight ratio of the vinyl-terminated polysiloxane to the hydrogen-containing polysiloxane is (1-9):1.
[0020] In a preferred embodiment of the present invention:
[0021] The weight ratio of component A to component B is (2-3):1;
[0022] In component A:
[0023] The weight ratio of the heat-resistant and anticorrosive composite filler to the composite film-forming material is 1:(2-5);
[0024] The weight ratio of the thermal insulation filler to the composite film-forming material is 1:(1-4);
[0025] The weight ratio of the composite ceramic powder to the composite film-forming material is 1:(3-7);
[0026] The weight ratio of the reinforcing filler to the composite film-forming material is 1:(2.5-5);
[0027] The anti-poisoning agent is 1-3wt% of the composite film-forming material;
[0028] The second solvent is 10-25% of the total weight of the composite film-forming material, the heat-resistant and corrosion-resistant composite filler, the thermal insulation filler, the composite ceramic powder and the reinforcing filler;
[0029] In component B:
[0030] The weight ratio of the vinyl-terminated polysiloxane to the hydrogen-containing polysiloxane is (4-9):1.
[0031] In a preferred embodiment of the present invention:
[0032] The composite film-forming material is obtained by compounding raw materials including vinyl-terminated polysiloxane and imide-modified polysiloxane; and / or,
[0033] The composite ceramic powder comprises the following components sintered at high temperature: metal alkoxide and imide-modified polysiloxane; preferably,
[0034] The imide-modified polysiloxane is prepared by the following method:
[0035] After reacting raw materials including allylamine and tetracarboxylic dianhydride to obtain an imide monomer, the imide monomer is subjected to a catalytic reaction with a biterminal silane hydrogen siloxane monomer under the catalysis of a catalyst to obtain the imide-modified polysiloxane; more preferably, the method comprises:
[0036] (1) subjecting the raw materials including allylamine, tetracarboxylic dianhydride and a first solvent to amidation reaction, and then subjecting the raw materials to high temperature reflux reaction, and after the reaction, washing, filtering and drying to obtain the imide monomer;
[0037] (2) catalytically reacting the imide monomer solution and the biterminal silane monomer solution under the catalysis of a catalyst, and after the reaction is completed, settling, washing, and drying to obtain the imide-modified polysiloxane.
[0038] The following solutions can be adopted:
[0039] The imide-modified polysiloxane is prepared by a two-step synthesis method: (1) preparing a bisallyl imide monomer: reacting allylamine and tetracarboxylic dianhydride in a molar ratio of (2.0-2.2):1, firstly performing an amide acidification reaction at room temperature, and then performing a high-temperature reflux reaction to generate an imide. After the reaction is completed, adding distilled water for washing, filtering, and drying to obtain an imide monomer; (2) preparing an imide-modified polysiloxane: mixing the imide monomer and a biterminal silane hydrogen siloxane monomer in a weight ratio of (1-5):1, using a Pt complex as a catalyst for a catalytic reaction, reacting for 6-8 hours, using methanol for precipitation, washing, and drying to obtain an imide-modified polysiloxane.
[0040] The structural formula of the imide-modified polysiloxane is:
[0041]
[0042] Wherein R1 is a phenyl-containing functional group, preferably one of phenyl, biphenyl, phenyl ketone, and 4,4'-(hexafluoroisopropylidene)diphenyl; n is 0 or 1; and m is 10-120, preferably 20-100.
[0043] The imide-modified polysiloxane of the present invention is an imide-modified polysiloxane containing terminal allyl groups. The introduction of the imide structure can improve the heat resistance, high-temperature ceramic formation rate and bonding strength of the film-forming material, and the allyl group can also undergo secondary cross-linking at high temperatures to improve the ablation resistance of the system.
[0044] In a preferred embodiment of the present invention:
[0045] The molar ratio of the allylamine to the tetracarboxylic dianhydride is (1.95-2.25):1, preferably (2.0-2.2):1; and / or,
[0046] The weight ratio of the tetraacid dianhydride to the first solvent is (0.05-0.08):1, preferably (0.065-0.075):1; and / or,
[0047] The weight ratio of the imide monomer to the biterminal siloxane monomer is (1-5):1, preferably (1.5-4.5):1; and / or,
[0048] The catalyst is a platinum complex, and the weight of the platinum element in the platinum complex is 0.5-2.5wt%, preferably 1.0-2.0wt%, of the imide monomer.
[0049] In a preferred embodiment of the present invention:
[0050] The tetracarboxylic dianhydride is a phenyl-containing tetracarboxylic dianhydride, preferably at least one of 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride; and / or,
[0051] The first solvent is glacial acetic acid; and / or,
[0052] The solvent of the imide monomer solution is at least one of tetrahydrofuran, N-methylpyrrolidone, dimethylformamide and dimethylacetamide. Preferably, the concentration of the imide monomer solution is 1-10wt%, more preferably 2-5wt%; and / or,
[0053] The dual-terminal siloxane monomer is 1,1,3,3-tetramethyldisiloxane and / or 1,1,3,3,5,5-hexamethyltrisiloxane; and / or,
[0054] The solvent of the biterminal siloxane monomer solution is at least one of tetrahydrofuran, toluene, dimethylformamide and dimethylacetamide. Preferably, the concentration of the biterminal siloxane monomer solution is 5-20wt%, more preferably 6-15wt%; and / or,
[0055] The catalyst is an isopropanol solution of chloroplatinic acid and / or a platinum complex coordinated by tetrahydrofuran.
[0056] In a preferred embodiment of the present invention:
[0057] The reaction temperature of the amidation reaction is 20-30° C. (room temperature), and / or the reaction time is 2-4 h; and / or,
[0058] The reaction temperature of the high temperature reflux reaction is 100-120° C., and / or the reaction time is 2-4 h; and / or,
[0059] The reaction temperature of the catalytic reaction is 55-65° C., and / or the reaction time is 6-8 hours.
[0060] In a preferred embodiment of the present invention:
[0061] The structural formula of the vinyl-terminated polysiloxane is: wherein R2 is methyl or ethyl, R3 is methyl or ethyl, p is 50-1000, preferably 100-900; and / or,
[0062] The weight ratio of imide-modified polysiloxane to vinyl-terminated polysiloxane in the composite film-forming material is 1:(2-10), preferably 1:(2-5); and / or,
[0063] The heat-resistant and anti-corrosion composite filler is obtained by compounding raw materials including nano titanium dioxide, nano boron carbide and mica iron oxide; preferably, the mica iron oxide accounts for 30-50% of the total weight of the heat-resistant and anti-corrosion composite filler, more preferably 35-45%, and / or, the weight ratio of the nano titanium dioxide to the nano boron carbide is 1:(2-5); and / or,
[0064] The thermal insulation filler comprises modified silica aerogel and hollow filler, preferably, the hollow filler is at least one of expanded vermiculite, vacuum ceramic microbeads, and floating beads, and / or, the weight ratio of the modified silica aerogel to the hollow filler is 1:(0.5-2); and / or,
[0065] The metal alkoxide is at least one of aluminum alkoxide, hafnium alkoxide and zirconium alkoxide, preferably aluminum sec-butoxide and / or hafnium butoxide, and / or, the weight ratio of imide-modified polysiloxane to metal alkoxide in the composite ceramic powder is 1:(0.05-0.35), preferably 1:(0.1-0.3); and / or,
[0066] The reinforcing filler comprises at least two of nano calcium sulfate whiskers, mullite fibers, glass fibers, and nano silicon dioxide; and / or,
[0067] The platinum complex catalyst is at least one of a platinum complex coordinated by tetrahydrofuran, a platinum catalyst coordinated by methylvinylsiloxane, and a platinum catalyst coordinated by diethyl phthalate; and / or,
[0068] The anti-poisoning agent is at least one of organic aluminum compounds, preferably at least one of aluminum isopropoxide, aluminum acetylacetonate, and diacetylacetonato isopropoxyaluminum; and / or,
[0069] The second solvent is at least one of xylene, toluene, tetrahydrofuran and solvent gasoline; and / or,
[0070] The hydrogen-containing polysiloxane may be any hydrogen-containing polysiloxane commonly used in the art. Preferably, the hydrogen-containing polysiloxane has a structural formula of: The content of Si-H is 0.5-2.5wt%, preferably 1-2wt%, and q is 10-80, preferably 20-60; more preferably, the viscosity of the hydrogen-containing polysiloxane is 15-100s, preferably 20-60s.
[0071] The second object of the present invention is to provide a method for preparing the high temperature resistant heat insulating repair material as described in one of the objects of the present invention.
[0072] The method for preparing the high temperature resistant strong bonding repair material of the present invention comprises:
[0073] The component A and the component B are prepared by mixing the respective components, and then the component A and the component B are mixed to prepare the repair material.
[0074] In a preferred embodiment of the present invention, the method comprises:
[0075] Preparation of composite ceramic powder: adding raw materials including metal alkoxide and imide-modified polysiloxane to a solvent, stirring and mixing, sintering at high temperature, and grinding after cooling to obtain the composite ceramic powder; preferably, the weight ratio of the imide-modified polysiloxane to the solvent is 1:(4-6), and / or the solvent is toluene, and / or the stirring speed of the stirring and mixing is 1500-2000rpm, and / or the stirring time is 30-60min, and / or the particle size after grinding is less than 200 mesh, and / or the high-temperature sintering includes pre-baking and high-temperature baking; more preferably, the baking temperature of the pre-baking is 90℃-110℃, and / or the baking time is 30-60min, and / or the high-temperature baking is carried out under a protective gas atmosphere, and / or the baking temperature of the high-temperature baking is 750℃-850℃, and / or the baking time is 5-15min;
[0076] The following solutions can be adopted:
[0077] The preparation method of the composite ceramic powder is as follows: 1) blending: the modified polysiloxane and the metal alkoxide are mixed according to a proportion, and an appropriate amount of toluene is added, and the mixture is uniformly mixed by high-speed stirring, the stirring speed is 1500-2000rpm, and the stirring time is 30-60min; 2) ceramicization: the mixture is placed in a metal tray, baked at 90℃-110℃ for 30-60min, and then transferred to a crucible, baked at 750℃-850℃ for 5-15min under a nitrogen atmosphere, and naturally cooled to room temperature; 3) grinding: the cooled ceramic material is ground into powder, and the fineness is ground to less than 200 mesh;
[0078] Preparation of component A: compounding the composite film-forming material, heat-resistant and corrosion-resistant composite filler, heat-insulating filler, composite ceramic powder, reinforcing filler, platinum complex catalyst and anti-poisoning agent to obtain component A;
[0079] The following solutions can be adopted:
[0080] The imide-modified polysiloxane, the vinyl-terminated polysiloxane, the heat-resistant and anticorrosive composite filler, the reinforcing filler (non-fibrous filler), and an appropriate amount of the second solvent are stirred at high speed for 30-60 minutes at a stirring speed of 1500-2000 rpm, and then the reinforcing filler (fibrous filler) is added and stirred at high speed for 20-40 minutes at a stirring speed of 1000-1500 rpm; finally, the above slurry is transferred to a kneader, and the heat-insulating filler, the platinum complex catalyst, the anti-poisoning agent and the remaining second solvent in the formula amount are added, mixed for 20-40 minutes, and the material is discharged to prepare component A; wherein the second solvent is added in batches, and the technicians in this field can adjust the adaptability according to the stirring state;
[0081] Preparation of component B: stirring and mixing the vinyl-terminated polysiloxane and the hydrogen-containing polysiloxane to obtain component B; preferably, the stirring rate of the stirring and mixing is 1000-1500 rpm, and / or the stirring time is 10-20 min;
[0082] Preparation of repair material: The repair material is prepared by mixing the component A and the component B.
[0083] The compounding described in the present invention refers to stirring and mixing evenly.
[0084] The third object of the present invention is to provide a high-temperature resistant thermal insulation repair material as described in one of the objects of the present invention or a high-temperature resistant thermal insulation repair material prepared by the method described in the second object of the present invention for use in repairing damaged parts of a thermal insulation composite material. Preferably, the thermal insulation composite material is a resin-based thermal insulation composite material.
[0085] The construction method of the repair material includes: 1) removing excess materials from the damaged part of the thermal insulation composite and grinding the damaged part; 2) mixing component A and component B of the repair material according to a proportion and manually stirring them evenly; 3) scraping the repair material on the damaged part, pressing the repair material fully during scraping to ensure that the repair material fully fills the damaged part, and then scraping the repair material along the surface of the thermal insulation composite and slightly higher than the surface of the thermal insulation composite; 4) after the repair material is left to solidify, grinding the repair material to make it flat and flush with the height of the thermal insulation composite to complete the repair.
[0086] The present invention provides a high-temperature resistant heat-insulating repair material that has good matching with heat-insulating composites, high bonding strength at high temperatures, and good anti-scouring performance, which solves the problems of poor high-temperature bonding strength of the repair material, easy debonding from the heat-insulating composite at high temperatures, and rapid ablation and thinning, so as to achieve rapid room-temperature repair of the heat-insulating composite. The repair material consists of two components, wherein component A is compounded with imide-modified polysiloxane / terminated vinyl polysiloxane composite film-forming material, heat-resistant and anti-corrosion composite filler, heat-insulating filler, composite ceramic powder, reinforcing filler, platinum complex catalyst, anti-poisoning agent, etc.; component B is compounded with terminal vinyl polysiloxane and hydrogen-containing polysiloxane; when used, component A and component B are evenly mixed and evenly scraped on the damaged part of the heat-insulating composite, and the repair material is polished and smoothed after solidification.
[0087] The repair material of the present invention can be cured at room temperature and has good high-temperature bonding strength (shear strength greater than 1.0MPa at 800℃×5min), low density, high-efficiency heat insulation and resistance to high-speed hot air flow erosion, etc. It has good matching properties with thermal insulation composites and can be used for rapid repair of damaged parts of thermal insulation composites. It can also be used as a thermal protection coating on the surface of high-speed aircraft to achieve the purpose of high-efficiency heat protection. At the same time, the repair material also has anti-corrosion properties and can also be used for the protection and repair of high-temperature parts such as high-temperature industrial kilns, large petrochemical storage tanks, industrial high-temperature pipelines, and high-temperature reactors. BRIEF DESCRIPTION OF THE DRAWINGS
[0088] Figure 1 is the XRD spectrum of the composite ceramic powder in Example 1;
[0089] Figure 2 This is a photo of the lightweight thermal insulation composite material after repair in Example 1;
[0090] Figure 3 This is a photograph of the shear specimen after high temperature heating when the repair material prepared in Example 1 was subjected to a high temperature shear strength test. DETAILED DESCRIPTION
[0091] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0092] The raw materials used in the examples and comparative examples of the present invention are all commercially available products.
[0093] [Example 1]
[0094] The high temperature resistant heat insulation repair material is composed of two components, component A and component B. The preparation methods of component A and component B are as follows:
[0095] The formula of component A of the high temperature resistant heat insulation repair material is: imide modified polysiloxane (20 parts by weight), terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are methyl, p is 800, 80 parts by weight) (Jinan Yingyu Chemical Co., Ltd.), nano silicon dioxide (15 parts by weight), nano titanium dioxide (4 parts by weight), nano boron carbide (8 parts by weight), mica iron oxide (8 parts by weight), mullite fiber (25 parts by weight), modified silicon dioxide aerogel (20 parts by weight) (Shijiazhuang Techeng New Material Technology Co., Ltd.), vacuum ceramic microbeads (25 parts by weight), composite ceramic powder (25 parts by weight), platinum complex coordinated by tetrahydrofuran (2.3 parts by weight, platinum content is 3wt%) (Shanghai Sishan Polymer Materials Co., Ltd.), aluminum isopropoxide (3 parts by weight), and xylene (50 parts by weight).
[0096] The preparation process of the above-mentioned component A is as follows: imide-modified polysiloxane, vinyl-terminated polysiloxane, nano-silicon dioxide, nano-titanium dioxide, nano-boron carbide, mica iron oxide, and composite ceramic powder are weighed according to the formula, and stirred at a high speed of 2000 rpm for 30 minutes; after stirring evenly, mullite fiber is added according to the formula ratio, and stirred at a high speed for 30 minutes at a stirring rate of 1000 rpm; finally, the above-mentioned slurry is transferred to a kneader, and the modified silica aerogel, vacuum ceramic microbeads, platinum complex coordinated by tetrahydrofuran, aluminum isopropoxide, and xylene in the formula amount are added, mixed for half an hour, and discharged, so as to prepare component A of the high-temperature resistant heat-insulating repair material. The solid content of component A is 82%.
[0097] The preparation process of the imide-modified polysiloxane in the above-mentioned component A is as follows: (1) 60 g of allylamine and 161.1 g of 3,3',4,4'-dibenzophenone tetracarboxylic dianhydride are dissolved in 2.5 L of glacial acetic acid, and stirred for reaction at room temperature (25±2° C.) for 2 h; then the temperature is raised to 120° C. under a nitrogen atmosphere and refluxed for 3 h. After the reaction is completed, water is added to precipitate after cooling to room temperature, filtered, and washed to obtain a monomer filter cake, which is heated and dried at 80° C. for 8 h to prepare a diallyl imide monomer DA-BTDA. (2) 40.59 g of diallyl imide monomer DA-BTDA was dissolved in 1.5 L of tetrahydrofuran. After complete dissolution, 35 ml of isopropanol solution of chloroplatinic acid (platinum content: 0.02 g / ml) (Shanghai Ke New Material Technology Co., Ltd.) was added and nitrogen was passed through. Then, a tetrahydrofuran solution of 1,1,3,3-tetramethyldisiloxane (13.12 g of siloxane monomer dissolved in 0.2 L of tetrahydrofuran) was added dropwise, followed by reaction at 60° C. for 6 h. After the reaction was completed, methanol was added for precipitation, suction filtration and drying to obtain an imide-modified polysiloxane, the structural formula of which is shown in the above formula (I), wherein R1 is a phenone group; n is 0; and m is 35.
[0098] The preparation process of the composite ceramic powder in the above component A is as follows: (1) Blending: Dissolve 10g of the above imide-modified polysiloxane and 2.5g of aluminum sec-butoxide in 50g of xylene, and mix them evenly by high-speed stirring at a stirring speed of 1500rpm and a stirring time of 60min; 2) Ceramics: Place the mixture on a metal tray, bake at 100°C for 30min, then transfer to a crucible, bake at 700°C for 10min under a nitrogen atmosphere, and cool naturally to room temperature; 3) Grinding: Grind the cooled ceramic into powder until the fineness is less than 200 mesh. The composite ceramic powder was subjected to X-ray diffraction analysis (XRD), and its spectrum is shown as follows: Figure 1 As shown, it indicates that inorganic ceramic powder has been formed.
[0099] Component B of the high temperature resistant heat insulation repair material is prepared by stirring at 1000 rpm for 20 minutes and is composed of terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are methyl, p is 800, 80 parts by weight) and hydrogen-containing polysiloxane, Si-H content is 1wt%, viscosity is 50s, 20 parts by weight) (Jinan Runbenxiang Chemical Co., Ltd.).
[0100] Component A and component B were mixed evenly at a weight ratio of 2.6:1 to obtain a high temperature resistant heat insulation repair material. The density of the repair material after curing was tested to be 0.47 g / cm 3 The shear specimens were prepared according to GB / T7124. After curing at room temperature, the room temperature shear strength was 2.3MPa; the high temperature shear strength at 800℃×5min was 1.2MPa.
[0101] The lightweight thermal insulation composite material was artificially damaged, and the damaged part was cleaned and then the above-mentioned high temperature resistant thermal insulation repair material was scraped on the damaged part. When scraping, the repair material was pressed on the damaged defect to make it fully contact with the thermal insulation composite material; and the surface of the repair material was slightly higher than the thermal insulation composite material. After it solidified, it was polished and shaped with sandpaper to make it coplanar with the lightweight thermal insulation composite material to complete the repair. After the repair, the material was intact, and there was no problem of interface debonding. The bonding strength was tested by the pull-out method according to GB / T5210, and the bonding strength was 1.1MPa, indicating that the lightweight thermal insulation composite material was damaged.
[0102] [Example 2]
[0103] The high temperature resistant heat insulation repair material is composed of two components, component A and component B. The preparation methods of component A and component B are as follows:
[0104] The formula of component A of the high temperature resistant heat insulation repair material is: imide modified polysiloxane (30 parts by weight), terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are methyl, p is 800, 70 parts by weight), nano calcium sulfate whisker (15 parts by weight), nano titanium dioxide (4 parts by weight), nano boron carbide (8 parts by weight), mica iron oxide (10 parts by weight), mullite fiber (25 parts by weight), modified silica aerogel (15 parts by weight), vacuum ceramic microbeads (30 parts by weight), composite ceramic powder (25 parts by weight), methyl vinyl siloxane coordinated platinum catalyst (0.53 parts by weight, platinum content is 15wt%) (Zhongxin Silicone Material Co., Ltd.), aluminum isopropoxide (2 parts by weight), xylene (44 parts by weight.
[0105] The preparation process of the above-mentioned component A is as follows: imide-modified polysiloxane, vinyl-terminated polysiloxane, nano-silicon dioxide, nano-calcium sulfate whisker, nano-boron carbide, mica iron oxide, and composite ceramic powder are weighed according to the formula, and high-speed stirring is adopted, and the stirring rate is 2000rpm for 30min; after stirring evenly, mullite fiber is added according to the formula ratio, and high-speed stirring is carried out for 30min at a stirring rate of 1000rpm; finally, the above-mentioned slurry is transferred to a kneader, and the modified silica aerogel, vacuum ceramic microbeads, methylvinylsiloxane coordinated platinum catalyst, isopropyl aluminum and xylene in the formula amount are added, and the material is discharged after mixing for half an hour, so as to prepare the high-temperature resistant heat insulation repair material component A. The solid content of component A is 84%.
[0106] The preparation process of the imide-modified polysiloxane in the above component A is the same as that in Example 1.
[0107] The preparation process of the composite ceramic powder in the above component A is the same as that in Example 1.
[0108] Component B of the high temperature resistant heat insulation repair material is prepared by stirring at 1000 rpm for 20 minutes with terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are methyl groups, p is 800, 80 parts by weight) and hydrogen-containing polysiloxane (Si-H content is 1wt%, viscosity is 50s, 20 parts by weight).
[0109] Component A and component B were mixed evenly at a weight ratio of 2.5:1 to obtain a high temperature resistant heat insulation repair material. The density of the repair material after curing was tested to be 0.53 g / cm 3 The shear specimens were prepared according to GB / T7124. After curing at room temperature, the room temperature shear strength was measured to be 2.2MPa; the high temperature shear strength at 800℃×5min was 1.5MPa.
[0110] The lightweight thermal insulation composite material was artificially damaged and repaired with the above-mentioned repair material, and the repair method was the same as that in Example 1. After the repair, the material was intact, and there was no problem of interface debonding. The bonding strength was tested by the pull-out method according to GB / T5210, and the bonding strength was 1.2 MPa, indicating that the thermal insulation composite material was damaged.
[0111] [Example 3]
[0112] The high temperature resistant heat insulation repair material is composed of two components, component A and component B. The preparation methods of component A and component B are as follows:
[0113] The formula of component A of the high temperature resistant heat insulation repair material is: imide modified polysiloxane (20 parts by weight), terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are ethyl, p is 600, 80 parts by weight), nano silicon dioxide (10 parts by weight), nano calcium sulfate whisker (10 parts by weight), nano titanium dioxide (4 parts by weight), nano boron carbide (8 parts by weight), mica iron oxide (8 parts by weight), mullite fiber (15 parts by weight), modified silicon dioxide aerogel (20 parts by weight), floating beads (15 parts by weight), composite ceramic powder (20 parts by weight), tetrahydrofuran coordinated platinum complex (2.43 parts by weight, platinum content is 3wt%), aluminum isopropoxide (3 parts by weight), and xylene (28 parts by weight).
[0114] The preparation process of the above-mentioned component A is as follows: imide-modified polysiloxane, vinyl-terminated polysiloxane, nano-silicon dioxide, nano-calcium sulfate whisker, nano-titanium dioxide, nano-boron carbide, mica iron oxide, and composite ceramic powder are weighed according to the formula, and stirred at a high speed of 2000 rpm for 50 minutes; after stirring evenly, mullite fiber is added according to the formula ratio, and stirred at a high speed for 30 minutes at a stirring rate of 1000 rpm; finally, the above-mentioned slurry is transferred to a kneader, and the modified silica aerogel, floating beads, tetrahydrofuran coordinated platinum complex, aluminum isopropoxide and xylene in the formula amount are added, mixed for half an hour, and discharged, so as to prepare component A of the high-temperature resistant heat-insulating repair material. The solid content of component A is 88%.
[0115] The preparation process of the imide-modified polysiloxane in the above-mentioned component A is as follows: (1) 60 g of allylamine and 216.8 g of 4,4'-(hexafluoroisopropylene) diphthalic anhydride are dissolved in 3 L of glacial acetic acid, and stirred for reaction at room temperature (25±2°C) for 2 h; then the temperature is raised to 120°C and refluxed for 4 h under a nitrogen atmosphere. After the reaction is completed, water is added to precipitate after cooling to room temperature, filtered, and washed to obtain a monomer filter cake, which is heated and dried at 80°C for 8 h to prepare the diallyl imide monomer DA-6FDA. (2) 53.78 g of diallyl imide monomer DA-6FDA was dissolved in 1.5 L of tetrahydrofuran. After complete dissolution, 35 ml of isopropanol solution of chloroplatinic acid (platinum content of 0.02 g / ml) was added and nitrogen was passed through. Then, a tetrahydrofuran solution of 1,1,3,3-tetramethyldisiloxane (13.12 g of siloxane monomer was dissolved in 0.2 L of tetrahydrofuran) was added dropwise, and then reacted at 60° C. for 8 h. After the reaction was completed, methanol was added for precipitation, suction filtration, and drying to obtain an imide-modified polysiloxane, the structural formula of which is shown in the above formula (I), wherein R1 is 4,4'-(hexafluoroisopropyl)diphenyl; n is 0; and m is 56.
[0116] The preparation process of the composite ceramic powder in the above-mentioned component A is as follows: (1) Blending: dissolve 10g of the above-mentioned imide-modified polysiloxane and 2.5g of hafnium butoxide in 50g of xylene, and mix them evenly by high-speed stirring at a stirring speed of 1500rpm and a stirring time of 60min; 2) Ceramics: place the mixture on a metal tray, bake it at 100°C for 30min, then transfer it to a crucible, bake it at 700°C for 10min under a nitrogen atmosphere, and cool it naturally to room temperature; 3) Grinding: grind the cooled ceramic into powder to a fineness of less than 200 mesh.
[0117] Component B of the high temperature resistant heat insulation repair material is prepared by stirring at 1000 rpm for 20 minutes with terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are ethyl groups, p is 600, 80 parts by weight) and hydrogen-containing polysiloxane (Si-H content is 1.2wt%, viscosity is 40s, 20 parts by weight).
[0118] Component A and component B were mixed evenly at a weight ratio of 2.5:1 to obtain a high temperature resistant heat insulation repair material. The density of the repair material after curing was tested to be 0.49 g / cm 3 The shear specimens were prepared according to GB / T7124. After curing at room temperature, the room temperature shear strength was measured to be 2.5 MPa; the high temperature shear strength at 800°C×5min was 1.3 MPa.
[0119] The lightweight thermal insulation composite material was artificially damaged and the above-mentioned repair material was used for scraping and repairing, and the specific method was the same as that in Example 1. After the repair, the material was intact, and there was no problem of interface debonding. The bonding strength was tested by the pull-out method according to GB / T5210, and the bonding strength was 1.1 MPa, indicating that the thermal insulation composite material was damaged.
[0120] [Example 4]
[0121] The high temperature resistant heat insulation repair material is composed of two components, component A and component B. The preparation methods of component A and component B are as follows:
[0122] The formula of component A of the high-temperature resistant heat-insulating repair material is: imide-modified polysiloxane (30 parts by weight), terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are ethyl groups, p is 600, 70 parts by weight), nano-silicon dioxide (10 parts by weight), glass fiber (5 parts by weight), nano-titanium dioxide (3 parts by weight), nano-boron carbide (15 parts by weight), mica iron oxide (12 parts by weight), mullite fiber (15 parts by weight), modified silica aerogel (15 parts by weight), floating beads (25 parts by weight) composite ceramic powder (15 parts by weight), diethyl phthalate coordinated platinum complex (4.5 parts by weight, platinum content 2wt%, Zhongxin Silicone Materials Co., Ltd.), aluminum isopropoxide (3 parts by weight), and xylene (38 parts by weight).
[0123] The preparation process of the above-mentioned component A is as follows: imide-modified polysiloxane, vinyl-terminated polysiloxane, nano-silicon dioxide, nano-titanium dioxide, nano-boron carbide, mica iron oxide, and composite ceramic powder are weighed according to the formula, and stirred at high speed at a rate of 2000 rpm for 50 minutes; after stirring evenly, glass fiber and mullite fiber are added according to the formula ratio, and stirred at high speed for 30 minutes at a rate of 1000 rpm; finally, the above-mentioned slurry is transferred to a kneader, and the modified silica aerogel, floating beads, diethyl phthalate coordinated platinum complex, aluminum isopropoxide, and xylene in the formula amount are added, mixed for half an hour, and discharged, so as to prepare component A of the high-temperature resistant heat-insulating repair material. The solid content of component A is 85%.
[0124] The preparation process of the imide-modified polysiloxane in the above-mentioned component A is as follows: (1) 60 g of allylamine and 147.1 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride are dissolved in 2 L of glacial acetic acid, and stirred for reaction at room temperature (25±2° C.) for 2 h; then the temperature is raised to 120° C. under a nitrogen atmosphere and refluxed for 4 h. After the reaction is completed, water is added to precipitate after cooling to room temperature, filtered, and washed to obtain a monomer filter cake, which is heated and dried at 80° C. for 8 h to prepare a diallyl imide monomer DA-BPDA. (2) 37.18 g of diallyl imide monomer DA-BPDA was dissolved in 1.5 L of tetrahydrofuran. After complete dissolution, 30 ml of isopropanol solution of chloroplatinic acid (platinum content of 0.02 g / ml) was added and nitrogen was passed through. Then, a tetrahydrofuran solution of 1,1,3,3,5,5-hexamethyltrisiloxane (22.76 g of siloxane monomer was dissolved in 0.2 L of tetrahydrofuran) was added dropwise, and then reacted at 60° C. for 8 h. After the reaction was completed, methanol was added for precipitation, suction filtration and drying to obtain an imide-modified polysiloxane, the structural formula of which is shown in the above formula (I), wherein R1 is biphenyl; n is 1; and m is 22.
[0125] The preparation process of the composite ceramic powder in the above-mentioned component A is as follows: (1) Blending: dissolve 10g of the above-mentioned imide-modified polysiloxane and 3.0g of hafnium butoxide in 50g of xylene, and mix them evenly by high-speed stirring at a stirring speed of 1500rpm and a stirring time of 60min; 2) Ceramics: place the mixture on a metal tray, bake it at 100°C for 30min, then transfer it to a crucible, bake it at 700°C for 10min under a nitrogen atmosphere, and cool it naturally to room temperature; 3) Grinding: grind the cooled ceramic into powder to a fineness of less than 200 mesh.
[0126] Component B of the high temperature resistant heat insulation repair material is prepared by stirring at 1000 rpm for 20 minutes with terminal vinyl polysiloxane (the structural formula is shown in the above formula (II), wherein R2 and R3 are ethyl groups, p is 600, 80 parts by weight) and hydrogen-containing polysiloxane (Si-H content is 1.2wt%, viscosity is 40s, 20 parts by weight).
[0127] Component A and component B were mixed evenly at a weight ratio of 2.5:1 to obtain a high temperature resistant heat insulation repair material. The density of the repair material after curing was tested to be 0.55 g / cm 3 The shear specimens were prepared according to GB / T7124. After curing at room temperature, the room temperature shear strength was measured to be 2.3MPa; the high temperature shear strength at 800℃×5min was 1.6MPa.
[0128] The lightweight thermal insulation composite material was artificially damaged and the above-mentioned repair material was used for scraping and repairing, and the specific repair method was the same as that in Example 1. After the repair, the material was intact, and there was no problem of interface debonding. The bonding strength was tested by the pull-out method according to GB / T5210, and the bonding strength was 1.1 MPa, indicating that the thermal insulation composite material was damaged.
[0129] [Comparative Example 1]
[0130] The repair material is prepared by referring to the method in the prior art CN105860828A. The repair material consists of two components, component A and component B. The preparation methods of component A and component B are as follows:
[0131] The formula of repair material component A is as follows: glycidylamine epoxy resin (12 parts by weight), silicone resin (13 parts by weight), glycidyl ester epoxy resin (10 parts by weight), titanium dioxide (4 parts by weight), fumed silica (0.5 parts by weight), ceramic microbeads (3 parts by weight), vermiculite (6 parts by weight), iron oxide (1 part by weight), boron phenolic resin powder (2 parts by weight), aramid staple fiber (1 part by weight), SiC (3 parts by weight), aluminum oxide (7 parts by weight), APP (5 parts by weight), and mica powder (5 parts by weight).
[0132] The preparation method of repair material component A is as follows: (1) Glycidylamine epoxy resin, silicone resin, and glycidyl ester epoxy resin are mixed in the above proportions, and then titanium dioxide, SiC, APP, mica powder, ceramic microbeads, vermiculite, and boron phenolic resin powder are added in the above proportions, and each filler is stirred and dispersed at a high speed of 2000 rpm for 15 minutes; (2) Under low speed stirring of 1000 rpm, iron oxide and fumed silica are added in proportion in turn, and then dispersed at a high speed of 2000 rpm for 15 minutes; component A is prepared.
[0133] The formula of component B of the repair material is as follows: triethanolamine modifier (10 parts by weight), polyamide-200 (15 parts by weight), 2-methyl-5-vinylpyridine (2 parts by weight), ethyl acetate (5 parts by weight), and anhydrous ethanol (5 parts by weight).
[0134] The preparation method of repair material component B is as follows: after the triethanolamine modifier is kept at a constant temperature of 45° C. for 1 hour, polyamide-200, 2-methyl-5-vinylpyridine, ethyl acetate and anhydrous ethanol are added in proportion to obtain a viscous liquid component B.
[0135] Component A and component B were mixed at a weight ratio of 1.82:1 to obtain a repair material with a measured density of 1.16 g / cm 3 The shear strength at room temperature is 9.8MPa. During the high temperature shear strength test, the sample debonds due to heat and the test result is 0MPa.
Claims
1. A high temperature resistant strong bonding repair material, characterized in that The repair material comprises component A and component B, wherein component A and component B are prepared from raw materials comprising the following components respectively: Component A includes a composite film-forming material, a heat-resistant and anticorrosive composite filler, a heat-insulating filler, a composite ceramic powder, a reinforcing filler, a platinum complex catalyst, an anti-poisoning agent, and a second solvent; Component B includes vinyl-terminated polysiloxane and hydrogen-containing polysiloxane; The weight ratio of component A to component B is (0.5-3):1; In component A: The weight ratio of the heat-resistant and anticorrosive composite filler to the composite film-forming material is 1:(1-9); The weight ratio of the thermal insulation filler to the composite film-forming material is 1:(1-6); The weight ratio of the composite ceramic powder to the composite film-forming material is 1:(2.5-10); The weight ratio of the reinforcing filler to the composite film-forming material is 1:(2-10); The weight of the platinum element in the platinum complex catalyst is 5-500ppm of the total weight of the A component; The anti-poisoning agent is 0.5-5wt% of the composite film-forming material; The second solvent is 5%-30% of the total weight of the composite film-forming material, the heat-resistant and corrosion-resistant composite filler, the thermal insulation filler, the composite ceramic powder and the reinforcing filler; In component B: The weight ratio of the vinyl-terminated polysiloxane to the hydrogen-containing polysiloxane is (1-9):
1.
2. The repair material according to claim 1, characterized in that: The weight ratio of component A to component B is (2-3):1; In component A: The weight ratio of the heat-resistant and anticorrosive composite filler to the composite film-forming material is 1:(2-5); The weight ratio of the thermal insulation filler to the composite film-forming material is 1:(1-4); The weight ratio of the composite ceramic powder to the composite film-forming material is 1:(3-7); The weight ratio of the reinforcing filler to the composite film-forming material is 1:(2.5-5); The anti-poisoning agent is 1-3wt% of the composite film-forming material; The second solvent is 10-25% of the total weight of the composite film-forming material, the heat-resistant and corrosion-resistant composite filler, the thermal insulation filler, the composite ceramic powder and the reinforcing filler; In component B: The weight ratio of the vinyl-terminated polysiloxane to the hydrogen-containing polysiloxane is (4-9):
1.
3. The repair material according to claim 1 or 2, characterized in that: The composite film-forming material is obtained by compounding raw materials including vinyl-terminated polysiloxane and imide-modified polysiloxane; and / or, The composite ceramic powder comprises the following components sintered at high temperature: metal alkoxide and imide-modified polysiloxane; preferably, The structural formula of the imide-modified polysiloxane is: Wherein R1 is a phenyl-containing functional group, preferably one of phenyl, biphenyl, phenyl ketone, and 4,4'-(hexafluoroisopropylidene)diphenyl; n is 0 or 1; and m is 10-120, preferably 20-100.
4. The repair material according to claim 3, characterized in that: The imide-modified polysiloxane is prepared by the following method: After reacting raw materials including allylamine and tetracarboxylic dianhydride to obtain an imide monomer, the imide monomer is subjected to a catalytic reaction with a biterminal silane hydrogen siloxane monomer under the catalysis of a catalyst to obtain the imide-modified polysiloxane; more preferably, the method comprises: (1) subjecting the raw materials including allylamine, tetracarboxylic dianhydride and a first solvent to an amidation reaction, and then subjecting the raw materials to a high-temperature reflux reaction. After the reaction, the raw materials are washed, filtered and dried to obtain the imide monomer; (2) catalytically reacting the imide monomer solution and the biterminal silane monomer solution under the catalysis of a catalyst, and after the reaction is completed, settling, washing, and drying to obtain the imide-modified polysiloxane.
5. The repair material according to claim 4, characterized in that: The molar ratio of the allylamine to the tetracarboxylic dianhydride is (1.95-2.25):1, preferably (2.0-2.2):1; and / or, The weight ratio of the tetraacid dianhydride to the first solvent is (0.05-0.08):1, preferably (0.065-0.075):1; and / or, The weight ratio of the imide monomer to the biterminal siloxane monomer is (1-5):1, preferably (1.5-4.5):1; and / or, The catalyst is a platinum complex, and the weight of the platinum element in the platinum complex is 0.5-2.5wt%, preferably 1.0-2.0wt%, of the imide monomer.
6. The repair material according to claim 4, characterized in that: The tetracarboxylic dianhydride is a phenyl-containing tetracarboxylic dianhydride, preferably at least one of 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl tetracarboxylic dianhydride and 4,4'-(hexafluoroisopropylene) diphthalic anhydride; and / or, The first solvent is glacial acetic acid; and / or, The solvent of the imide monomer solution is at least one of tetrahydrofuran, N-methylpyrrolidone, dimethylformamide and dimethylacetamide. Preferably, the concentration of the imide monomer solution is 1-10wt%, more preferably 2-5wt%; and / or, The dual-terminal siloxane monomer is 1,1,3,3-tetramethyldisiloxane and / or 1,1,3,3,5,5-hexamethyltrisiloxane; and / or, The solvent of the biterminal siloxane monomer solution is at least one of tetrahydrofuran, toluene, dimethylformamide and dimethylacetamide. Preferably, the concentration of the biterminal siloxane monomer solution is 5-20wt%, more preferably 6-15wt%; and / or, The catalyst is an isopropanol solution of chloroplatinic acid and / or a platinum complex coordinated by tetrahydrofuran; and / or, The reaction temperature of the amidation reaction is 20-30° C., and / or the reaction time is 2-4 h; and / or, The reaction temperature of the high temperature reflux reaction is 100-120° C., and / or the reaction time is 2-4 h; and / or, The reaction temperature of the catalytic reaction is 55-65° C., and / or the reaction time is 6-8 hours.
7. The repair material according to claim 3, characterized in that: The structural formula of the vinyl-terminated polysiloxane is: wherein R2 is methyl or ethyl, R3 is methyl or ethyl, p is 50-1000, preferably 100-900; and / or, The weight ratio of imide-modified polysiloxane to vinyl-terminated polysiloxane in the composite film-forming material is 1:(2-10), preferably 1:(2-5); and / or, The heat-resistant and anti-corrosion composite filler is obtained by compounding raw materials including nano titanium dioxide, nano boron carbide and mica iron oxide; preferably, the mica iron oxide accounts for 30-50% of the total weight of the heat-resistant and anti-corrosion composite filler, more preferably 35-45%, and / or, the weight ratio of the nano titanium dioxide to the nano boron carbide is 1:(2-5); and / or, The thermal insulation filler comprises modified silica aerogel and hollow filler, preferably, the hollow filler is at least one of expanded vermiculite, vacuum ceramic microbeads, and floating beads, and / or, the weight ratio of the modified silica aerogel to the hollow filler is 1:(0.5-2); and / or, The metal alkoxide is at least one of aluminum alkoxide, hafnium alkoxide and zirconium alkoxide, preferably aluminum sec-butoxide and / or hafnium butoxide, and / or, the weight ratio of imide-modified polysiloxane to metal alkoxide in the composite ceramic powder is 1:(0.05-0.35), preferably 1:(0.1-0.3); and / or, The reinforcing filler comprises at least two of nano calcium sulfate whiskers, mullite fibers, glass fibers, and nano silicon dioxide; and / or, The platinum complex catalyst is at least one of a platinum complex coordinated by tetrahydrofuran, a platinum catalyst coordinated by methylvinylsiloxane, and a platinum catalyst coordinated by diethyl phthalate; and / or, The anti-poisoning agent is at least one of organic aluminum compounds, preferably at least one of aluminum isopropoxide, aluminum acetylacetonate, and diacetylacetonato isopropoxyaluminum; and / or, The second solvent is at least one of xylene, toluene, tetrahydrofuran and solvent gasoline.
8. A method for preparing a high temperature resistant strong bonding repair material according to any one of claims 1 to 7, characterized in that The method comprises: The component A and the component B are prepared by mixing the respective components, and then the component A and the component B are mixed to prepare the repair material.
9. The method according to claim 8, characterized in that The method comprises: Preparation of composite ceramic powder: adding raw materials including metal alkoxide and imide-modified polysiloxane to a solvent, stirring and mixing, sintering at high temperature, and grinding after cooling to obtain the composite ceramic powder; preferably, the weight ratio of the imide-modified polysiloxane to the solvent is 1:(4-6), and / or the solvent is toluene, and / or the stirring speed of the stirring and mixing is 1500-2000rpm, and / or the stirring time is 30-60min, and / or the particle size after grinding is less than 200 mesh, and / or the high-temperature sintering includes pre-baking and high-temperature baking; more preferably, the baking temperature of the pre-baking is 90℃-110℃, and / or the baking time is 30-60min, and / or the high-temperature baking is carried out under a protective gas atmosphere, and / or the baking temperature of the high-temperature baking is 750℃-850℃, and / or the baking time is 5-15min; Preparation of component A: compounding the composite film-forming material, heat-resistant and corrosion-resistant composite filler, heat-insulating filler, composite ceramic powder, reinforcing filler, platinum complex catalyst and anti-poisoning agent to obtain component A; Preparation of component B: stirring and mixing the vinyl-terminated polysiloxane and the hydrogen-containing polysiloxane to obtain component B; preferably, the stirring rate of the stirring and mixing is 1000-1500 rpm, and / or the stirring time is 10-20 min; Preparation of repair material: The repair material is prepared by mixing the component A and the component B.
10. Use of the high temperature resistant strong adhesive repair material as described in any one of claims 1 to 7 or the high temperature resistant strong adhesive repair material prepared by the method as described in claim 8 or 9 in repairing damaged parts of a thermal insulation composite material, preferably, the thermal insulation composite material is a resin-based thermal insulation composite material.
